Rumah Lanting di Sungai Sambas Desa Sumber Harapan Kecamatan Sambas Kalimantan Barat (Etnografi Budaya Sungai) - Fitri Ardianti; Donatianus BSE Praptantya; Hasanah Hasanah (Balale' : Jurnal Antropologi, 2021)
This study aimed to find about the history of the Lanting house and more deeply understand the characteristics of the Lanting houses, floating on the river in Sumber Harapan Village. This study used a qualitative approach with the ethnography research method. Triangulation method was used to test the validity of the data. According to Malinowski’s functional theory, all cultural activities actually intend to satisfy a series of instincts of human beings that are related to their entire lives. Thus, the techniques of data collection were observation, interviews, and documentation.The results of this study indicate that the Lanting House not only functions as a place to live, but also develops as a place of business. There are two functions of the Lanting House in Sumber Harapan Village such as the function of a residence that provides protection from disturbances, arise from the environment around them. The second was not only used as shelter, but also as a place of business as a fulfillment of their lives because of the changing life patterns. In addition, each Lanting house has similar form one from another, which has a simple room pattern.